Rethinking Regionalism: Institutional Change, Security, and Development in the Sahel’s Alliance of States - AbdulQadir Al-Ameen; Sani Shehu (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2026)
This article examines the institutional evolution of Niger, Mali, and Burkina Faso from externally driven regional forums to the creation of the Alliance of Sahel States (AES), a confederate alliance established in 2023. This research analyzes the draws on institutionalist and neoclassical realist frameworks, as well as qualitative document analysis, empirical data,, and comparative review. The study finds that persistent insecurity, developmental stagnation, and the withdrawal of international actors are key drivers for the move towards greater regional autonomy. The article shows the advantages and the risks of the confederate structure of the AES by comparing it with previous and parallel African regional organizations. The findings highlight the propositions for sovereignty, governance, and external partnerships and the importance of inclusive regional governance in preventing democratic backsliding. Policy recommendations are provided to national governments, regional organizations, and international partners to promote stability, resilience, and development in the Sahel region. Keywords: Sahel, regional integration, confederation, security, development, Niger, Mali, Burkina Faso.